Data Privacy and Security in a Globalized Digital World: Legal Perspectives on Cross-Border Data Flows - Garima, Dr. Shreya (Journal of Informatics Education and Research, 2025)
As information systems become a weapon for controlling the future, we are living in a time when they are becoming a new weapon of war. The flow of data across national borders is a vital resource for economic and informational development in any country. Cross-border data flows are increasingly important in international trade due to the frequent transfer of employee and customer data across borders. Using cross-border data exchange as a case study, this paper discusses its privacy implications. As neither the Digital Personal Data Protection Act of 2023 nor the Information Technology Act of 2000 provide any protection for cross-border data transfers, the report discusses a cross-border data protection policy. Particularly, the Digital Personal Data Protection Act, 2023, provides no information about how data can be transferred between countries or processed for data principals outside of the country. When some countries restrict data movement abroad by enacting laws concerning data localization, they negatively affect international trade and development. The question then arises: What types of data, and in what quantities, are nations required to restrict? Here is a comparison of the General Data Protection Regulation of the European Union, the Asia Pacific Economic Cooperation Privacy Rules, and the Privacy Shield Framework between the EU and US. To conclude, this paper suggests the need for uniform laws to protect cross-border data and their universal applicability.